Vascular flora and phytogeographical links of the Carabaya Mountains, Peru - Gonzáles, Paúl (2018)
Studies of floristic composition and plant species richness in tropical mountains support their recognition as areas of high biological diversity, and therefore of their importance for plant conservation. Here, we present data on the flora of the high Andes of eight sites centered in the Carabaya mountains, and also provide a floristic comparison with nine other floras within Peru and northern Bolivia. The study area includes 506 species of vascular plants, grouped in 203 genera and 66 families. The highest species richness was found in two families: Asteraceae and Poaceae, which collectively encompass 37% of all species. Other important families were Caryophyllaceae, Fabaceae, Malvaceae, Brassicaceae, Caprifoliaceae, Gentianaceae, Plantaginaceae and Cyperaceae. The most diverse genera were Senecio, Calamagrostis, Poa and Nototriche. Perennial herbs were the dominant growth form. The vascular flora of the Carabaya Mountains is closely related to those of other regions of southern Peru. Also, more than half of all vascular plants registered for the Carabaya Mountain occur in the Andean region of Bolivia, which shows the undoubted geophysical and phytogeographical connection of the Carabaya and the Bolivian Apolobamba Mountains. This study also shows that there is still a need for more extensive plant collecting and future exploration, since the Carabaya, as other parts of Peru’s high Andes are subject of dramatic change that may threaten these plant populations.